Influence of Teachers’ Work Conditions on Classroom Management Practices - Impuesto, Rose (Journal of Interdisciplinary Perspectives, 2024)
This study investigated the impact of teachers' work conditions on classroom management practices in public elementary schools. A mixed-method sequential explanatory design was used, involving surveys from 328 teachers across 22 public schools in Pasig City through stratified random sampling and interviews with ten teachers. Quantitative analysis revealed significant positive correlations between teachers' demographic factors (age, sex, and designation) and work conditions, such as workload, student academic performance, school rules, facilities, and resources. Regression analysis further indicated that workload, student behavior, school policies, facilities, and leadership support significantly influence classroom management. Qualitative findings highlighted the complex relationship between work conditions and teachers' classroom practices. The findings suggest that improving work conditions, such as reducing teacher workload, enhancing school facilities, and providing stronger leadership support, can significantly improve classroom management practices in public elementary schools. Moreover, tailored policies that address teachers' demographic factors and the specific challenges in their work environment are crucial for fostering effective classroom management. These insights can guide policymakers and school administrators in creating more supportive environments for teachers, ultimately improving student outcomes and overall school performance.